Факторы влияния чеховского текста на пьесы Александра Марданя „Антракт” и „Аншлаг” (отказ от власти прецедент¬ных текстов или возвращение к ним?) - Sibirnaya, Maria (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
This research is dedicated to the issue of the classical drama reception, which is supposed to be canonical, used in the play of Odessian playwright Alexandr Mardan. The concept of modern times appears in Mardan’s plays through the literary and cultural inheritance of the past. The usage of Chekhov’s motives in both plays we deal with — Antract and Anshlag seems not only to resemble the form used in the mass culture, but also stylization and reinterpretation of the classic, which appear here as modern literary devices through which the interpretation of canonical drama occurs. In both plays one can observe a lack of presentation of classical motives in a modern, revolutionary form, there is no retrieval to the precedent writings with the final idea of elaborating on Chekhov thoughts. Furthermore, the classical motives are used for the reinterpretation of how theater may influence the modern human being and how endless the attempts to interpret the classic are.